Linguistic representation - Iglesias, T; Iglesias-Rozas, Maria Teresa (1979)
﻿ The study is concerned with some aspects of the philosophical development of Russell and Wittgenstein in the period in which their doctrines interacted closely with each other. The questions investigated -nay be summarised as follows: (i) What does it mean to say that language represents reality in an isomorphic manner ? (ii) How is it possible for language to represent reality isomorphically and yet be related to it in such a way that the relation it has in virtue of its sense is independent of the relation it has in virtue of its truth? In answering these questions, particular attention has been paid to Russell's unpublished Manuscript Epistemology (1913) because of the impact it had on Wittgenstein, who severely criticised it. These criticisms began to emerge, as an alternative to Russell's views, in 'Notes on Logic' and in the other pre-Tractarian writings. It is in the Tractatus, eventually, that the two-fold relation between language and reality, which Russell's position left unexplained, is accounted for, by virtue of the distinction form/structure. The following are the central theses of this study: (a) Although Russell and Wittgenstein share the assumption of linguistic isomorphic representation, their isomorphisms are totally different, since Wittgenstein makes the distinction form/structure and Russell does not; (b) Wittgenstein's development from the earlier writings to the Tractatus may be viewed in terms of the emergence of distinctions such as, the world as substance/the world as fact, possibilities/ actualities, form/structure, which lie at the heart of the Tractatus and serve to substantiate its central semantic doctrine concerning the language-reality relation of representation; (c) since the Tractatus maintains the principle that 'sense is independent of the facts' (i.e., that there is an independence or priority of sense over truth) then a proposition's relation to reality cannot be accounted for by means of ostension, for such an account involves the denial of the principle; (d) the divergence between Russell and Wittgenstein as regards the main concern of the Tractatus, centres on the divergence of their views concerning the vagueness of ordinary language; (e) a central aspect of the unity of Wittgenstein's entire philosophy, as regards the internal relation- ship between language and reality, lies in his conception of form.